PERAN EMPLOYEE RELATIONS DALAM MENINGKATKAN ENGAGEMENT KARYAWAN DI ERA REMOTE WORKING (JURNAL BADATI, 2024)
This study examines the evolving role of employee relations in enhancing employee engagement during the remote working era. Through a systematic literature review of publications from 2019-2024, this research analyzes the transformation of employee relations strategies, engagement dynamics, and their implications in virtual work environments. The findings reveal a significant shift towards digital-based employee relations with a 92% technology adoption rate and an increase in engagement levels from 65% to 82%. Key factors contributing to successful engagement include work flexibility (35%) and technological support (28%). The study also identifies notable improvements in employee well- being, with a 35% reduction in stress levels and a 42% increase in work-life balance. Virtual team building programs showed the highest ROI (145%), followed by mental health support (132%) and digital skills development (128%). However, challenges persist in technology integration (45%), communication barriers (42%), and time zone coordination (28%). This research contributes to both theoretical understanding and practical implementation of employee relations strategies in remote working contexts, offering insights for organizations adapting to the evolving workplace landscape.